Improving the vocalization latency (vl) of the undergraduates of faculty of science, university of jaffna: a neuro–cognitive analysis on raudamatizing morpho syntactic elements in english - Paranthaman, V. (University of Jaffna, 2012)
This research paper is primarily based on poor readers’ neuro cognitive activation of their vocalization through externally provided scaffolding strategy. Combining the two neuro-cognitive aspects vocalization–latency and raudamatization, the research probes into an essential investigation which reflects the necessity of separating the poor L2 readers from the learner population and providing them an externally prepared intervention programme to activate their vocalization latency. Vocalization Latency and raudamatization are the primary micro level reading strategies employed by the readers. Fluent readers are well developed in these skills. But this is not the case with the low–proficiency L2 readers. These readers are under developed in these micro–skills. As a result, most of these poor readers are word-bound and become frustrated in academic reading. Having such readers as the primary informants the research procedure introduces an intervention for the experimental group. The study investigates the feasibility and usability of the intervention among the low profiling L2 readers. Amalgamating Carver’s rauding model and the reading while listening methods, the prepared intervention is experimented with the informants in the experimental group. The duration of the intervention is one month and altogether it includes six rauding lessons. These six raduing lesions are prepared by the researcher to activate the vocalization Latency of the low–proficiency L2 readers whose raudamatization skills are primarily weak. The time count taken during the vocalization Latency test is the major data in this research. Reduction in the time used during the post VLT is treated as symptom of improving the vocalization Latency of the informants.
Keywords: Neuro-cognitive activation; Scaffolding; Vocalization latency; Raudamatization; Low proficiency L2 readers; Academic reading; Intervention